IT encyclopaedia.com - Diwan, Parag (Ed.); Kaushik, Sanjay (Ed.); Suri, R K (Ed.) (New Delhi Pentagon Press, 2001)
IT Encyclopaedia is a ten volumed set and it cover the information about fundamentals of information technology,Information system management, Software Engineers,computer networks and ecommerce,multimedia system,graphical user interface Enterprise Resource planning,E-commrece Information Technology laws and Dictionary of IT terms are the main features
Contents:v.1.Fundamentals of Information Technology -v.2.Information system management -v.3.Software engineering -v.4.Computer networks and E-Commerce -v.5.Multimedias -v.6.Graphical User Interface -v.7.Enterprise resource planning -v.8.E-Commerce -v.9.Information Technology Laws -v.10 Dictionary of IT Terms
Keywords: Computers; Computer networks; Operating systems (Computers); Internet (Computers network); Information technology-Encyclopaedias and dictionaries; Software engineering; Information resources management; Electronic Commerce